Update on nutritionally variant streptococci ( Streptococcus defectives and Streptococcus adjacents) - Ruoff, Kathryn L. (Clinical microbiology newsletter, 1990)
Much new information concerning nutritionally variant streptococci has appeared in the literature since the publication of Roberta B Carey's very competent review of these bacteria in the September 1984 issue of Clinical Microbiology Newsletter. The reader is referred to her article for an in-depth discussion of earlier work on this subject, which has been briefly summarized in the "Background" section in this article. The remainder of the present article will deal with more recent developments in the study of nutritionally variant streptococci.